2007
DOI: 10.1182/blood-2006-11-050526
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe aplastic anemia with antithymocyte globulin and cyclosporin A with or without G-CSF in adults: a multicenter randomized study in Japan

Abstract: We report the results of a randomized study to elucidate whether addition of granulocyte colony-stimulating factor (G-CSF) to immunosuppressive therapy is valuable for the treatment of severe aplastic anemia (SAA) in adults. A total of 101 previously untreated patients (median age, 54 years; range, 19 to 75 years) were randomized to receive antithymocyte globulin (ATG) and cyclosporin A (CyA) (G-CSF؊ group) or ATG, CyA, and G-CSF (G-CSF؉ group). In the G-CSF؉ group, the hematologic response rate at 6 months wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 31 publications
5
88
0
3
Order By: Relevance
“…4,34 One study from Japan comparing immunosuppression with or without G-CSF reported a lower relapse rate in the G-CSF group. 5 This was not confirmed in a large European multi-center trial. 4 One must also take into account the potential risk that G-CSF increases the incidence of secondary clonal disorders.…”
Section: Hematopoietic Growth Factors As Prophylaxis Of Infections Ormentioning
confidence: 91%
See 2 more Smart Citations
“…4,34 One study from Japan comparing immunosuppression with or without G-CSF reported a lower relapse rate in the G-CSF group. 5 This was not confirmed in a large European multi-center trial. 4 One must also take into account the potential risk that G-CSF increases the incidence of secondary clonal disorders.…”
Section: Hematopoietic Growth Factors As Prophylaxis Of Infections Ormentioning
confidence: 91%
“…The individual risk of a patient is mainly determined by the neutrophil, and monocyte counts. [2][3][4][5][6][7][8] During the past two decades, infection-related mortality and invasive fungal infections decreased. 2 However, infections are still the major threat for patients with severe or very severe AA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All six trials reported overall mortality, five of them at 100 days, 4,16,17,32,34 (Figure 2). Sensitivity analysis for mortality rate at 100 days showed a higher RR (favoring control) with adequate allocation concealment and generation, RR 1.57 (95% CI 0.44-5.55, 3 trials) compared to unclear methods, RR 1.15 (95% CI 0.34-3.84, 2 trials), without a statistically significant result or difference between the subgroups.…”
Section: Primary Outcomementioning
confidence: 99%
“…Duplicate publication -1 trial 31 RCTs included in the meta-analysis (n =6) 4,16,17,[32][33][34] © F e r r a t a S t o r t i case analysis were extracted. For the main analysis, all trials were pooled.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%